Can social support predict health-promoting behaviors among community-dwelling older adults? - Leila Khami; Seyedeh Ameneh Motalebi; Fatemeh Mohammadi; Maryam Momeni; Akram Shahrokhi (Social Health and Behavior, 2020)
Introduction: Because health-promoting behavior is one of the major determinants of health, this study was conducted to determine whether social support predicts health-promoting behaviors in elderly people living in Tabriz, Iran. Methods: In this descriptive and cross-sectional study, 180 elderly people referring to the health complexes in Tabriz, Iran, were selected using a random cluster sampling method. Data were collected using demographic questionnaires, the Health-Promoting Lifestyle Profile II, and the Multidimensional Perceived Social Support Scale. Data were analyzed using stepwise multiple linear regression models. Results: The mean age of 180 elderly people who participated in the study was 66.9 ± 5.74 years. The results of multiple regression indicated that education (B = 8.98, P < 0.001) and perceived social support (B = 0.45, P < 0.014) explained ~29% of changes in health-promoting behaviors among the elderly. Conclusion: Given the predictive role of perceived social support in health-promoting behaviors, establishing or strengthening supportive social networks seems to be one of the effective factors in promoting the elderly's health.